Blinded outcomes and angina assessment of coronary bioresorbable scaffolds: 30-day and 1-year results from the ABSORB IV randomised trial. Issue 10157 (27th October 2018) - Stone, Gregg W; Ellis, Stephen G; Gori, Tommaso; Metzger, D Christopher; Stein, Bernardo; Erickson, Matthew; Torzewski, Jan; Williams, Jerome; Lawson, William; Broderick, Thomas M; Kabour, Ameer; Piegari, Guy; et al.
Summary: Background: Previous studies showed more adverse events with coronary bioresorbable vascular scaffolds (BVS) than with metallic drug-eluting stents (DES), although in one randomised trial angina was reduced with BVS. However, these early studies were unmasked, lesions smaller than intended for the scaffold were frequently enrolled, implantation technique was suboptimal, and patients with myocardial infarction, in whom BVS might be well suited, were excluded. Methods: In the active-controlled, blinded, multicentre, randomised ABSORB IV trial, patients with stable coronary artery disease or acute coronary syndromes aged 18 years or older were recruited from 147 hospitals in five countries (the USA, Germany, Australia, Singapore, and Canada). Enrolled patients were randomly assigned (1:1) to receive polymeric everolimus-eluting BVS (Absorb; Abbott Vascular, Santa Clara, CA, USA) with optimised implantation technique or cobalt-chromium everolimus-eluting stents (EES; Xience; Abbott Vascular, Santa Clara, CA, USA). Randomisation was stratified by diabetic status, whether patients would have been eligible for enrolment in the previous ABSORB III trial, and site. Patients and clinical assessors were masked to randomisation. The primary endpoint was target lesion failure (cardiac death, target vessel myocardial infarction, or ischaemia-driven target lesion revascularisation) at 30 days, tested for non-inferiority with a 2·9% margin for the risk difference. Analysis was by intention to treat. The trial is registered with ClinicalTrials.gov, number NCT02173379, and is closed to accrual. Findings: Between Aug 15, 2014, and March 31, 2017, we screened 18 722 patients for eligibility, 2604 of whom were enrolled. 1296 patients were assigned to BVS, and 1308 patients were assigned to EES. Follow-up data at 30 days and 1 year, respectively, were available for 1288 and 1254 patients with BVS and for 1303 and 1272 patients with EES. Biomarker-positive acute coronary syndromes were present in 622 (24%) of 2602 patients, and, by angiographic core laboratory analysis, 78 (3%) of 2893 of lesions were in very small vessels. Target lesion failure at 30 days occurred in 64 (5·0%) patients assigned to BVS and 48 (3·7%) patients assigned to EES (difference 1·3%, upper 97·5% confidence limit 2·89; one-sided pnon-inferiority =0·0244). Target lesion failure at 1 year occurred in 98 (7·8%) patients assigned to BVS and 82 (6·4%) patients assigned to EES (difference 1·4%, upper 97·5% confidence limit 3·4; one-sided pnon-inferiority =0·0006). Angina, adjudicated by a central events committee at 1 year, occurred in 459 (36·8%) patients assigned to BVS and 494 (39·1%) patients assigned to EES (difference –2·3%, 95% CI –6·1% to 1·5%; one-sided pnon-inferiority =0·0001; two-sided psuperiority =0·2404). Device thrombosis within 1 year occurred in nine (0·7%) patients assigned to BVS and four (0·3%) patients assigned to EES (p=0·1586). Interpretation: Polymeric BVS implanted with optimised technique in an expanded patient population resulted in non-inferior 30-day and 1-year rates of target lesion failure and angina compared with metallic DES. Funding: Abbott Vascular.